Constructing Meaning in Tafsir of Sufism: From Personal Intuition to Social Interconnectedness - Irfan Nurzaman; Zia Azkamalaki Muhamad; Zumrotun Khasanah; Eni Zulaiha (Tunas Harapan Ummat Foundation, 2025)
The study of Sufi interpretation emerged as a response to the need to understand the Qur'an. in a more in-depth and holistic manner. However, this approach is not free from controversy. The urgency of studying Sufi interpretation is also increasing along with the increasing interest towards spirituality and the search for a deeper meaning in life among Muslims modern. The purpose of this study is to identify Sufi interpretations, including its meaning, origins, limitations, disputes, differences with philosophical interpretations, indications Tafsir book that contains Sufic orientation, and its advantages and disadvantages. This study using the literature review method. This includes collecting and analyzing literature which is relevant about Sufi tafsir to gain a comprehensive understanding of approaches, techniques, and the role of Sufi figures in interpreting the Quran. This study found, after conducting an analysis of various relevant literature, that the interpretation Sufis, who emphasize inner meaning and rich mystical experience, offer a deep and spiritual perspective on the understanding of the Qur'an. This interpretation also shows how the verses of the Quran can be interpreted through experience personal and spiritual intuition to increase closeness to God. In the process interpret the holy verses, Sufi interpretation emphasizes the importance of intuition, mystical experience and personal closeness to God. This study shows that this method is successful reveals the inner and symbolic meanings of the Quran, which helps the readers deepen their spiritual understanding and enrich their experiences with Lord